DNA testing in sexual assault cases: When do the benefits outweigh the costs?. (June 2019) - Davis, Robert C.; Wells, William
Highlights: Nearly 40% of cases, after CODIS hits, did not result in an arrest or prosecution. Legal follow-up was based on victims' availability, willingness, and creditability. In nearly all cases where arrests were made, suspects were convicted and sentenced. Findings suggest that federal programs provide worthwhile returns on investments. Abstract: Objectives: We examined 1200 sexual assault cold cases from Denver, Colorado to ascertain the rate of successful prosecution in which there was a DNA suspect match and the cost per conviction. Results: Nearly 40% of the cases in which there was a DNA match failed to result in an arrest or prosecution primarily because victims were uncooperative or their testimony was judged to be unreliable. Other factors affecting conviction included crime context, victim availability, and the ability of the defendant to mount a consensual sex defense. Once an arrest had been made, however, the conviction rate exceeded 90%. We estimate that Denver's sexual assault DNA testing program cost roughly $16, 000 per conviction. Conclusion: Our results lend strong support to the value of testing sexual assault kits (SAKs) even in cold cases. This suggests that programs such as Federal Solving Cold Cases with DNA Program are well worth the investment.